2017
DOI: 10.4208/cicp.oa-2016-0183
|View full text |Cite
|
Sign up to set email alerts
|

DNS Study on Vortex and Vorticity in Late Boundary Layer Transition

Abstract: Vortex and vorticity are two correlated but fundamentally different concepts which have been the central issues in fluid mechanics research. Vorticity has rigorous mathematical definition (curl of velocity), but no clear physical meaning. Vortex has clear physical meaning (rotation) but no rigorous mathematical definition. For a long time, many people treat them as a same thing. However, based on our high-order direct numerical simulation (DNS), we found that first, “vortex” is not “vorticity tube” or “vortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In 1989, Robinson [11,12] pointed out that the association between regions of strong vorticity and actual vortices can be rather weak in the turbulent boundary layer, especially in the near wall region. Similar conclusions were obtained by Wang et al [13] a vortex is not necessarily the congregation of vorticity lines, but a dispersion in most three dimensional cases, which means the vorticity in a vortex is not necessarily larger than the surrounding area in many 3D cases.…”
supporting
confidence: 87%
“…In 1989, Robinson [11,12] pointed out that the association between regions of strong vorticity and actual vortices can be rather weak in the turbulent boundary layer, especially in the near wall region. Similar conclusions were obtained by Wang et al [13] a vortex is not necessarily the congregation of vorticity lines, but a dispersion in most three dimensional cases, which means the vorticity in a vortex is not necessarily larger than the surrounding area in many 3D cases.…”
supporting
confidence: 87%
“…Y. Wang et al (2017) found in the direct numerical simulation results that not only the vorticity and the direction of the vorticity were completely separated from the darts, but there was also a region with strong rotation but small vorticity, and the vorticity was large in the non-rotating area.…”
Section: Contact Zhengren Wu Zhengren_wu@163commentioning
confidence: 97%
“…However, Green [6] gave more detailed and different exposition, the early transition constitutes an event where vorticity is abruptly focused and ejected in a concentrated plume out of the surface layer; then it can be described as comprising a reorganization and local concentration of the existing vorticity field in a transition state. There are also other voices, vortex is not necessarily congregation of vorticity lines, but dispersion in most three dimensional cases [7], which means the vorticity in a vortex is not necessarily larger than the surrounding area in 3D cases. [8] defined vortices by using vortex tubes which has been proved to be inaccurate by many researchers [5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many researchers track vortex by high concentration of vorticity. That is why some researchers hold the view that the transition is a process with vorticity increase while others believe the total vorticity is constant during the transition process [6,12,13]. So what is the true symbol of vortex generation and growth in the transition from laminar flow to turbulence?…”
Section: Introductionmentioning
confidence: 99%